Imperatives of Public Private Partnership (PPP) in the Development of Education in Nigeria - Ikati, Lawrence (International Journal of Educational Management, 2025)
Public Private Partnership in the area of education is an initiative that contribute towards the development of education in Nigeria. Over the decades, education expansion and development has been a major concern to stakeholders in the education system. Complaints of lack of infrastructure, access, equity, quality, enrolment and provision of instructional facilities have posed a very serious challenge. The paper reviewed the role and contributions of Public-Private Participation (PPP) in the development of education, the challenges confronting the smooth operations of organizations in providing support services to this very important sector of Nigeria economy and guidelines guiding their activities. The paper concluded and suggested among others that due to the huge cost of education there is need for Public-private partnership in the provision of educational opportunities